Analisis Biaya Pembelian Bahan Baku Terhadap Jumlah Produksi Pada CV. Shaniqua Marigold Bamboo Di Rangkasbitung - Bambang Pujo Purwoko; Ratna Handayani; Yumhi .; Jauhar Latifah (E-Journal Studia Manajemen, 2013)
Purchasing is one of the important functions in the success of the company's production, because this function has the responsibility to obtain raw materials at the quantity and quality is good and according to need. The study population was all over raw material purchasing data since the founding of the company and the sample is a raw material purchasing data and the amount of production for 10 months ie from January to October 2010 using the research instrument Likert scale (1-5). Data analysis techniques used are (1) the correlation coefficient, (2) the coefficient of determination, and (3) testing the hypothesis by using t test. The results showed that there is a strong relationship between the cost of purchase of raw materials and production quantities.